An uncommon case of bacteremia caused by Lancefieldella parvula in an oncological patient. (December 2022) - Cobo, Fernando; Pérez-Carrasco, Virginia; García-Salcedo, José A.; Navarro-Marí, José María
Abstract: We report an uncommon case of bacteremia due to Lancefieldella parvula isolated in pure culture. We present a 72 year-old-man affected with cancer admitted with abdominal pain due to a parietal rupture of the urinary bladder. After surgical treatment, the patient developed fever and two sets of blood cultures yielded a pure culture of an anaerobic microorganism identified as L. parvula (formerly Atopobium parvulum ) by MALDI-TOF MS, and confirmed by 16S rRNA gene sequencing. The isolate was susceptible to all antibiotics and the outcome was finally successful. Bacteremia due to L. parvula is an uncommon disease and, in that case, MALDI-TOF MS was an useful tool for the initial identification. Highlights: Lancefieldella parvula has been rarely associated with bacteremia. The patient had some risk factors for anaerobic bacteremia. MALDI-TOF MS provided a correct species identification. The isolate showed susceptibility to all antimicrobials.